2015
DOI: 10.1063/1.4931173
|View full text |Cite
|
Sign up to set email alerts
|

Polarization force-induced changes in the dust sheath formation

Abstract: The modifications arising in the dusty plasma sheath structure due to the presence of polarization forces acting on the dust grains are investigated. The corresponding appropriate Bohm criterion for sheath formation is obtained. It is found that the critical Mach number, beyond which the dusty plasma electrostatic sheath sets in, decreases whenever the polarization effects become important. In addition, when the polarization force dominates over the electrical one, the dust plasma sheath cannot set in. This ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It can set an upper limitation of the dust grain size beyond which the dusty plasma may not support any nonlinear excitations. The seath structure in dusty plasma gets also modified due to the polarization force which was investigated by Mayout et al [7]. The critical Mach number was determined with the help of modified Bohm criterion [8].…”
Section: Introductionmentioning
confidence: 99%
“…It can set an upper limitation of the dust grain size beyond which the dusty plasma may not support any nonlinear excitations. The seath structure in dusty plasma gets also modified due to the polarization force which was investigated by Mayout et al [7]. The critical Mach number was determined with the help of modified Bohm criterion [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bandyopadhyay et al 6 showed that an increase of the polarization force, for a given value of Mach number, leads to an increase (reduction) in the amplitude (width) of the solitary DA waves. More recently, Mayout et al 7 studied the modifications arising in the dusty plasma sheath formation due to the presence of polarization forces acting on the dust grains. They showed that the critical Mach number, beyond which the dusty plasma electrostatic sheath sets in, decreases when the polarization effects increase.…”
Section: Introductionmentioning
confidence: 99%
“…When the values of the reduced charge of dust grain are between 2 and 4 within the OML theory 32) in collisionless and unmagnetized plasma, the polarization force and the charge gradient force are of comparable magnitude are discussed by Khrapak et al 33,34) The polarization force represents the deformation of the Debye sphere around dust particles caused by non-uniform plasma. The dust grain will be acted by the polarization force when dust grains immersed in non-uniform plasma and the charge of the dust grain is constant, 24,[35][36][37][38][39][40][41][42][43][44]…”
Section: Introductionmentioning
confidence: 99%